Peroxidase activities in root segments of wheat genotypes under osmotic stress - Csiszár, Jolán (Acta Biologica Szegediensis, 2008)
One week old Triticum aestivum lines with different drought tolerance were subjected to polyethylene glycol (PEG 6000) treatment reaching 600 mOsm osmotic stress on the 13th day. Plant growth parameters, water status, soluble and cell wall-bound peroxidase (POD) activities were measured on the 15th day. While only small differences was found in the total peroxidase activities determined by either guaiacol or syringaldazine, the activities of some POD isoenzymes detected by benzidine substrate showed significant changes. The total density of soluble POD-containing fractions was higher in the drought stress tolerant Plainsman and Kobomugi cultivars due to osmotic stress than in controls. In Öthalom and Cappelle Desprez cultivars however, most of the soluble POD isoenzymes worked at lower level and only two isoenzymes showed enhanced activities after the PEG treatment. The changes of POD activities in the soluble fractions are in good correlation with the abiotic stress tolerance of wheat genotypes. The enzyme fraction bound covalently to cell wall showed a different isoenzyme pattern.